KETERIKATAN KERJA DAN PERILAKU INOVATIF KARYAWAN BADAN PENGUSAHAAN KAWASAN SABANG - Fairuz Fairuz; Abdul Rahman Lubis; Syafruddin Chan (FEB - Unsyiah, 2018)
This study aims to examine and analyze the effect of work attachment and job involvement on innovative behavior and its impact on the Employees Performance of Sabang Free Trade And Ports Authority. Population in this research was all employees at Sabang Free Trade And Ports Authority, which was 135 people. Sampling in this study was using census method because it involves the entire population. Data analysis techniques used in this study was The Structural Equation Modeling (SEM) of statistical software package AMOS 22.0 for testing the hypothesis. Proof of Hypothesis was done by using indicator of CR and P value. Because of the 5 verifikatif hypotheses tested in this study have CR value above 1.96 and P value smaller than 0.05, then all hypotheses tested rejected Ho and received H1. In other words, job involvement and job attachment have the effect to improve employee performance as long as the independent variable can be improved by the manager of Sabang Free Trade And Ports Authority. The intervening variable that innovative behavior has no influence to increase the dependent variable with other words means that the improvement of employee's performance will be better done by increasing the Job Involvement and the direct working attachment without involving innovative behavior variable